Service provision satisfaction of under- and postgraduate students at the Medical School Library of the University of Cape Town - Ntseane, Ronan Keabetswe (Department of Knowledge and Information Stewardship, 2024)
The effectiveness of libraries and information institutions is judged by the services they provide to their users. In order to function satisfactorily, these institutions should ensure that they satisfy the wants and needs of users, based on the demands of lecturers, classroom input and the need to augment what one already knows. For this to happen, libraries should try to have the necessary resources like books and journals, as well as being able to provide other services like the interlibrary loans, short loan collections, databases and competent staff, to name just a few.